Mitochondrial disease, hypertrophic cardiomyopathy and cutaneous lupus in an infant with food hypersensitivity - E Estrada-Reyes; D Lopez-Gallegos; E Faugier-Fuentes; M Pardo-Castañeda; E Barragán- Perez; I Nuñez-Barrera; M Sanchez-Ruiz; S Nuñez-Barrera; G Ramon-Garcia (Global Journal of Rare Diseases - Peertechz Publications, 2020)
This paper describes a 4 month-old-girl with food allergies, mitochondrial disease, cutaneous lupus, and hypertrophic cardiomyopathy. She suffered from infectious pericarditis due to Coxsakie virus as a complication. She additionally presented bicytopenia (hemoglobin levels 8.9 g/dL, platelets 127 x 103 / µL), high lactate levels (5mmol/L), seizures, hypertrophic cardiomyopathy. This was suggestive of mitochondrial disease. Specific IgE levels were positive for milk, patch tests were positive for milk and soy, with a persistency of symptoms with extensively hydrolyzed formula as well as an amino acid-based formula. A chicken-based formula was well tolerated. Coenzyme Q10 levels were low (0.29L). Low Coenzyme Q10 levels in mitochondrial patients have been found as well as in allergic diseases. We suggest that food hypersensitivity should be ruled out in mitochondrial patients with low Coenzyme Q10 levels.